ANALISIS YURIDIS PELANGGARAN PRINSIP FIDUCIARY DUTY OLEH DIREKSI YANG MELAKUKAN RANGKAP JABATAN DALAM PERSEROAN TERBATAS - Rumondang Sihite; Appe Hutauruk; Mardiman Sane; Fendi Maruba Parlindungan Hutahaea (LPPM STIH Awang Long, 2026)
The principle of fiduciary duty is an obligation that requires directors to manage the company in good faith, prudence, loyalty, and solely in the best interests of the company. In practice, directors who hold concurrent positions have the potential to create conflicts of interest that can reduce independence and increase the risk of violations of fiduciary obligations. This study aims to examine the legal regulations regarding the principle of fiduciary duty for directors who hold concurrent positions in limited liability companies and analyze the forms of fiduciary duty violations and their legal responsibilities based on Supreme Court Decision Number 1005 K/Pdt/2016. This study uses a normative legal research method. Legal materials are analyzed qualitatively through legal interpretation and legal reasoning. The results of the study indicate that in Supreme Court Decision Number 1005 K/Pdt/2016, the actions of directors who issue corporate guarantees without the approval of the Board of Commissioners are declared as a violation of the principle of fiduciary duty so that directors are held personally and jointly responsible for losses suffered by the company. This study concludes that it is necessary to strengthen legal regulations regarding fiduciary duty, clarify regulations regarding conflicts of interest due to dual positions, and implement the principles of good corporate governance more comprehensively to increase legal certainty, accountability in company management, and protection for shareholders and other stakeholders.